Rural Tourism as One of the Priority Factors for Sustainable Development of Rural Territories in Kazakhstan - TLEUBAYEVA, Aitolkyn (Journal of Environmental Management and Tourism; Vol 9 No 6 (2018): JEMT Volume IX Issue 6(30) Fall 2018DO - 10.14505//jemt.v9.6(30).21, 2019)
The article analyzes the state of agriculture in the Republic of Kazakhstan, the author analyzes tourism facilities in the Akmola region to clarify the characteristics and extent of rural tourism promotion in Kazakhstan, including in Astana, suggested ways to develop rural tourism.